1 and 2 Timothy and Titus to guard the deposit - Hughes, R. Kent; Chapell, Bryan (Wheaton, IL Crossway, 2000)
Includes bibliographical references and indexes. Contents : 1 and 2 Timothy / R. Kent Hughes; Titus / Bryan Chapell
Keywords: Bible. N.T. Pastoral Epistles -- commentaries